2021
DOI: 10.3390/ani11092680
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Using House Cricket (Acheta domesticus) or Mulberry Silkworm (Bombyx mori) Pupae Meal to Replace Poultry Meal in Canine Diets Based on Health and Nutrient Digestibility

Abstract: There has been increasing interest in using insects as sustainable protein sources for humans and animals. Therefore, this study aimed to explore the possibility of substituting poultry meal with house cricket (Acheta domesticus: AD) or mulberry silkworm (Bombyx mori: BM) pupae. Fifty healthy adult mixed-breed dogs were selected and divided into five experimental groups, which were fed, in amounts based on daily energy requirement, with a control diet, a diet with 10% AD, with 20% AD, with 7% BM, or with 14% B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…• In canine fed a tropical house cricket diet, there was a small increase in blood urea nitrogen and hemoglobin. Areerat et al (2021) value ranked third after soybean meal and B. mori. In vitro protein digestibility of A. domesticus was higher than housefly pupae, black soldier fly larvae and pupae, yellow mealworm, lesser mealworm, and six spot roach (Bosch et al, 2014).…”
Section: A Domesticus (House Cricket) As Animal Feedmentioning
confidence: 99%
“…• In canine fed a tropical house cricket diet, there was a small increase in blood urea nitrogen and hemoglobin. Areerat et al (2021) value ranked third after soybean meal and B. mori. In vitro protein digestibility of A. domesticus was higher than housefly pupae, black soldier fly larvae and pupae, yellow mealworm, lesser mealworm, and six spot roach (Bosch et al, 2014).…”
Section: A Domesticus (House Cricket) As Animal Feedmentioning
confidence: 99%
“…In the study of Freel et al [ 103 ], it was found that BSFL meal and BSFL oil are well-tolerated by dogs, and their consumption does not have any physiological effects that would be of concern. Based on these data, BSFL meal and oil did not affect overall health, so they can be safely included in the dogs’ diet.…”
Section: Digestibilitymentioning
confidence: 99%
“…Animal diets generally contain soybean meal or fish meal as a protein source; however, they do not support sustainable and sufficient feed production, and vary in chemical composition (Areerat et al . 2021). Therefore, exploring sustainable feed alternatives is crucial for animal production and maintenance.…”
Section: Introductionmentioning
confidence: 99%